PHYSIOTHERAPY CLINIC REHABILITATION TECHNICAL PLANNING ON FOUNDATION OF PENDIDIKAN ANAK CACAT IN JEMBER - Tatang Maulana Maliq; Paksitya Purnama Putra; Saifuridzal Saifuridzal (UPT Penerbitan Universitas Jember, 2022)
The Disabled Children's Education Foundation is a private educational institution at the primary to secondary level that provides educational programs for students with disabilities in Jember Regency. This year, school administrators and foundations have a planned program, namely to rehabilitate YPAC's office buildings and student dormitories to be converted into physiotherapy clinics. The problem faced by these educational institutions is that they do not have technical personnel in spatial planning, plan drawings and budget plans as planning documents. For this reason, it is necessary to provide assistance in terms of technical planning, in the hope of realizing an effective and efficient rehabilitation plan for the physiotherapy clinic building infrastructure. Initial discussions were conducted to find out the problems, types of clinical services and solutions. After the initial discussion, a condition survey, design, and calculation of the budget plan was carried out. The design of the building is planned according to the function and purpose of its use, namely physiotherapy services for both students with disabilities and also the general public, so that ease of access needs to be prioritized. In addition, the design also focuses on the area of ​​​​the room openings so that the management is more efficient and the health condition of the room is better. The Budget Plan is also prepared according to the existing budget and is carried out efficiently and according to the expected quality. Keywords : Physiotherapy Clinic, Design, Budget Plan.